Views of leaders in under-represented and equity-denied communities on organ and tissue donation in Nova Scotia, Canada, in light of the Human Organ and Tissue Donation Act: a qualitative descriptive study - Nelofar Kureshi; Matthew Weiss; Stephen Beed; Robin Urquhart; Cynthia Kendell; Jade Dirk; Wendy Cordoba (BMJ Open, 2023)
Objective To explore the views of underserved and equity-denied communities in Nova Scotia, Canada, regarding organ and tissue donation and deemed consent legislation.Design A qualitative descriptive study was undertaken, employing both interviews and focus groups.Setting The province of Nova Scotia, Canada—the first jurisdiction in North America to implement deemed consent legislation for organ and tissue donation.Participants Leaders of African Nova Scotian, Lesbian, Gay, Bisexual, Trans, Queer, Two Spirit (LGBTQ2S+) and Faith-based communities (Islam and Judaism) were invited to participate (n=11). Leaders were defined as persons responsible for community organisations or in other leadership roles, and were purposively recruited by the research team.Results Through thematic analysis, four main themes were identified: (1) alignment with personal values as well as religious beliefs and perspectives; (2) trust and relationships, which need to be acknowledged and addressed in the context of deemed consent legislation; (3) cultural competence, which is essential to the roll-out of the new legislation and (4) communication and information to combat misconceptions and misinformation, facilitate informed decision-making, and mitigate conflict within families.Conclusions Leaders of African Nova Scotian, LGBTQ2S+ and Faith-based communities in Nova Scotia are highly supportive of deemed consent legislation. Despite this, many issues exemplify the need for cultural competence at all levels. These findings should inform ongoing implementation of the legislation and other jurisdictions considering a deemed consent approach to organ and tissue donation.